To Construe a Constitution: Constitutional Pluralism - Borusevičiūtė, Miranda (Teisė, 2024)
The article explores the methodology of constitutional interpretation proposed by constitutional pluralism as one of the forms of ‘living’ constitutionalism. The article analyzes the main arguments of constitutional pluralism, then goes on to examine the conceptual structure of the debate between ‘living’ constitutionalism and originalism, and proceeds to investigate the importance of the two approaches to constitutional interpretation for Lithuanian legal scholarship. The article does not propose to choose one or the other theory to be adopted to construe the meaning of the Lithuanian Constitution. The article supports the idea of creating new theories of constitutional interpretation, theories that would combine the main elements of the two approaches to constitutional interpretation.